Characterization and Utilization of Sulphuric Acid and Bitter Leaf Extract Activated Carbon from Rice Husk for Zn(II) Adsorption - Ilesanmi Osasona; Ujiro Bestow Kanuhor (Indonesian Journal of Chemistry, 2021)
The world is clamoring for green synthetic modes of scientific and technological operations. From this point of view, an attempt was made to prepare activated carbon from rice husk using aqueous bitter leaf extract and a mineral acid (H2SO4) separately. The surface characteristics and the adsorption properties of the activated carbons from both methods were compared. The effects of adsorption variables on the adsorption of Zn(II) by bitter leaf extract activated carbon (RHAC1) and H2SO4 activated carbon (RHAC2) were conducted through batch studies. The morphological characterization revealed RHAC1 to be fibrous, more porous and contained finer particles than the chemical-activated counterpart. The role of hydroxyl and carbonyl groups in the adsorption of Zn(II) was pivotal. The optimum pH values for the adsorption of Zn(II) by both samples was 7. The adsorption kinetics and equilibrium isotherm obeyed Elovich and Freundlich models respectively while the evaluated Langmuir qmax were 71.47 and 67.12 mg g–1 for RHAC1 and RHAC2 respectively. The thermodynamic parameters revealed that the process was endothermic and spontaneous at all evaluated temperatures. Therefore, bitter leaf aqueous extract, as an activating agent for carbon production, could serve as a better or close substitute for the less environment-friendly H2SO4.